Determinants of knowledge sharing / Roslina Abd Hamid - Abd Hamid, Roslina (2017)
Knowledge sharing is the process of transform individual knowledge to organizational knowledge (Nonaka, 1994; Foss et al., 2010) which can help the organization to get maximum outcomes from the employees. The study was conducted at Universiti Sains Malaysia (USM) Pulau Pinang. The questionnaires were distributed to 351 respondents from various departments which are Jabatan Pendaftar, Jabatan Bendahari, Jabatan Sains Kaji Hayat each and 51 online surveys were sent to Pusat lnovasi dan Pentadbiran Awam. The complete answered and usable questionnaires were 132. After all the questionnaires was collected, a computer software which was called Statistical Package of Social Science (SPSS) version 22 had been used in order to analyze the data and checked the possible relationships between culture, reciprocal relationship, reward, self-efficacy and shared goals with knowledge sharing among the administration employees. The objective of this study was to study the predictors of knowledge sharing. From the finding, reward, self-efficacy and shared goals have a significant relationship towards knowledge sharing. The administration employees in USM Pulau Pinang feel that reward, self-efficacy and shared goals are the factors that encourage them to share knowledge among them. In conclusion, the organization should focus on rewards, self-efficacy and shared goals to ensure that the employees always motivated to share the knowledge among themselves.